3-(5-(1H-imidazol-1-yl) pent-1-en-1-yl)-9-ethyl-9H-carbazole: synthesis, characterization (IR, NMR), DFT, antimicrobial-antioxidant activities and docking study. Issue 23 (19th December 2022) - Ünver, Yasemin; Süleymanoğlu, Nevin; Ustabaş, Reşat; Bektaş, Kadriye İnan and Bektaş, Ersan and Güler, Halil İbrahim
Abstract: 3-(5-(1 H -imidazol-1-yl) pent-1-en-1-yl)-9-ethyl-9 H -carbazole called as compound 1 was synthesized and characterized by proton and carbon-13 nuclear magnetic resonance ( 1 H- and 13 C- NMR) and Fourier transform infrared (FTIR) spectroscopic methods. Density Functional Theory/Becke, 3-parameter (DFT/B3LYP), for compound 1 were performed with 6-311++G(d, p) method. Optimized geometry, frontier molecular orbitals (HOMO; highest occupied molecular orbital; LUMO: lowest unoccupied molecular orbital), IR and NMR parameters of compound 1 were obtained. The evaluations reveal that the calculation results support the experimental results. In addition, the antimicrobial (a microwell dilution method) and antioxidant activities (2, 2-Diphenyl-1-picrylhydrazyl (DPPH), 2, 2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS) ferric ion reducing antioxidant power (FRAP) of compound 1 were evaluated. According to the results obtained, it showed higher antimicrobial activity (Minimal inhibition concentration (MIC): 78.12 µg/mL) against B. subtilis subsp. Spizizenii . Morever, molecular docking studies were carried out to investigate the interactions of an antimicrobial agent on some important enzymes played important roles in nucleic acid (Deoxyribo nucleic acid (DNA) synthesis, cell wall synthesis, protein synthesis, and metabolism etc. The compound 1 was strongly bound to tyrosyl-tRNA synthetase enzyme (binding energy: −11.18 and Ki : 6.37 nM) and Beta-Ketoacyl-Acp Synthase III enzyme (binding energy: −10.29 and Ki : 28.47 nM). Communicated by Ramaswamy H. Sarma